Territory selection of breeding Golden Eagles Aquila chrysaetos in a low-density population (Avocetta, 2024)
Territory selection by birds of prey is an essential process influencing survival and productivity. For Golden Eagle Aquila chrysaetos, research in Europe has focused primarily upon migrating and high-density populations, and rarely on the territory selection in low-density populations. We analysed Golden Eagle breeding sites in Central Apennines (Italy), spanning from 29 sites in 1980 up to 38 sites in 2020, verifying in 4 different years (1980, 1990, 2000 and 2020) their status of occupancy or vacancy, through cross-checking data from available literature and field observations. In the chosen years, each site was characterized by land use and neighbouring distances variables, to individuate the presence of a possible common selection process. The different protection status of each area (unprotected or Natural/National Parks) was tested, assuming that habitat protection could have positive effects on Eagles’ territory selection. The so obtained panel data was statistically analysed by means of t-test, χ2 test and probit models. In one hand, Golden Eagles in the Apennines showed a continuous recolonization of territories, including seven previously vacant and two undiscovered sites. On the other hand, half of the vacant sites remain unoccupied. Our results suggest that Golden Eagles, in a low-density population, tend to minimize the effect of lower quality habitats by choosing a breeding territory which can guarantee low intra-specific interferences: 35% of 2020 breeding pairs have, at least, one nearby vacant territory. Depending on the quality of the available breeding habitat, Individual Adjustment Hypothesis (IAH) supports or replaces Habitat Heterogeneity Hypothesis (HHH).
Keywords: breeding behaviour; Central Apennines; birds of prey; raptors; population density; population dynamic